PHOTOSYNTHESIS CHARACTERISTICS OF ICE ALGAE WITH SPECIAL EMPHASES ON TEMPERATURE AND LIGHT CONDITIONS (EXTENDED ABSTRACT) (16th Symposium on Polar Biology) - スズキ, ヨシヒロ; クドウ, サカエ; タカハシ, マサユキ; SUZUKI, Yoshihiro; KUDOH, Sakae; TAKAHASHI, Masayuki (National Institute of Polar Research, 1995)
P(論文) departmental bulletin paper